A comprehensive strategy for the early treatment of COVID-19 with azithromycin/hydroxychloroquine and/or corticosteroids: Results of a retrospective observational study in the French overseas department of Réunion Island - Arthur Dubernet; Kevin Larsen; Laurie Masse; Jérôme Allyn; Emilie Foch; Lea Bruneau; Adrien Maillot; Marie Lagrange-Xelot; Vincent Thomas; Marie-Christine Jaffar-Bandjee; Loraine Gauzere; Loic Raffray; et al. (Journal of Global Antimicrobial Resistance, 2020)
Background: This study aimed to evaluate the prognosis of COVID-19 patients in Reunion Island, with a particular focus on the management of patients with hypoxemic pneumonia. Methods: This retrospective observational study was conducted from 11 March to 17 April 2020 at the only hospital authorized to manage patients with COVID-19 in Reunion Island. Results: Over the study period, 164 out of 398 patients (41.2%) infected with COVID-19 were admitted to Félix Guyon University Hospital. Of these, 36 (22%) developed hypoxemic pneumonia. Patients with hypoxemic pneumonia were aged 66 [56–77] years, 69% were male and 33% had hypertension. Ten patients (27.8%) were hospitalized in intensive care unit (ICU). Hydroxychloroquine/azithromycin treatment was associated with a lower ICU admission rate (P = 0.008). None of the 6 patients treated with corticosteroids were hospitalized in ICU (P = 0.16). There were no deaths at follow up (minimum 80 days). Conclusions: Despite the risk profile of COVID-19 patients with severe hypoxemic pneumonia, the mortality rate of the disease in Reunion Island was 0%. This may be due to the care bundle used in our hospital (early hospitalisation, treatment with hydroxychloroquine/azithromycin and/or corticosteroids, non-invasive respiratory support, etc).